Role of Phenobarbitone Maintenance Therapy in Asphyxiated Neonate with Encephalopathy to Control Seizure- A Randomized Clinical Trial (Bangladesh Journal of Child Health, 2022)
Background: Seizures after perinatal asphyxia may worsen brain injury. Phenobarbital (PHB) is commonly prescribed anticonvulsant worldwide to control seizure in asphyxiated neonates. The evidence of the best use of maintenance drugs is limited.Objective: To assess the effectiveness of phenobarbitone maintenance therapy in asphyxiated neonates with seizure.Material & Methods: A total of 79 asphyxiated neonates (HIE-II/ III), ³35 weeks were enrolled from January 2019 -January 2020 in this randomized clinical trial where cases were categorized into three groups. Group A received phenobarbitone 4mg/ kg/day twice daily for 6 weeks and Group B received 2mg/kg/day once daily for 2 weeks while Group C didn’t receive any anti-seizure medication after acute management. Clinical and electrophysiological study was done at discharge, one and half month of age. Data were analyzed by SPSS version 20.Result: Mean age in days was 0.96 ± 1.77 in Group-A, 0.66 ± 1.20 in Group-B and 0.55 ± 1.30 in Group-C. Both Group A and C had seizure in 33.34% and 12.5% in group B at 1½ month. During discharge most of the cases had normal EEG, EEG abnormalities were found in 25% cases in group B, 16.67% in group C and 8.33% in group A. At 1 ½ month, EEG abnormality was found more among group C (33.34%) than group A (25%) and B (25%) which was statistically insignificant.Conclusion: This study concluded that early discontinuation of phenobarbitone after acute management may not increase the risk of clinical and electrographic seizure in future.BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 162-167